Helicobacter pylori and anemia: a community-based cross-sectional study among adults in Southern Brazil Helicobacter pylori e anemia: um estudo transversal de base populacional entre adultos no Sul do Brasil - Iná S. Santos; Gicele Costa Minten; Neiva C. J. Valle; Giovana Costa Tuerlinckx; José Boccio; Domingo Andrés Barrado; Alessandra Banaszeski da Silva; Guilherme Augusto Reissig Pereira (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2009)
To investigate the association between Helicobacter pylori and anemia, a community-based cross-sectional study was conducted among 18-45 year old users of the 31 primary health care units in Pelotas, Southern Brazil. Interviews using a structured questionnaire were carried out in waiting rooms during two work shifts. Anemia (hemoglobin < 11g/dL among pregnant women, < 12g/dL among women and < 13g/dL among men) was diagnosed from capillary blood (HemoCue) and H. pylori by means of a 13C-UBT. Information on socio-demographic, behavioral and biological characteristics was collected. Logistic and linear regression analyses were carried out, taking into account aggregated primary health care units. A total of 1,117 respondents fulfilled the inclusion criteria (losses/refusals: 8.1%). Prevalence of anemia was 20.6% (18.2-23.2%) and of H. pylori, 70.7% (68.0-73.6%). After allowing for age, sex and skin color the odds ratio for anemia among those who were diagnosed H. pylori positive was 0.94 (0.70-1.27). After allowing for sex, skin color, family monthly income, age, and smoking, the reduction in hemoglobin among H. pylori positive respondents was 0.07g/dL (-0.24-0.11; p = 0.4). There is no association between H. pylori and anemia among adults attending primary health care units in Southern Brazil. Helicobacter pylori tem sido apontado como causa de anemia. Para investigar essa associação, estudo transversal de base populacional foi realizado entre adultos (18-45 anos de idade), usuários das 31 unidades básicas de saúde (UBS), em Pelotas, Sul do Brasil. Entrevistas com questionários estruturados foram feitas nas salas de espera, em dois turnos de trabalho. Anemia (hemoglobina < 11g/dL entre gestantes, < 12g/dL entre mulheres adultas e < 13g/dL entre homens) foi diagnosticada em sangue capilar (HemoCue). H. pylori foi identificado por 13C-Urea Breath Test. Foram coletadas informações sócio-demográficas, comportamentais e biológicas. Análise por regressão logística e linear, levando em conta a agregação por UBS. Dos 1.117 elegíveis, foram perdidos ou recusaram-se participar 8,1%. A prevalência de anemia foi 20,6% (18,2-23,2%) e H. pylori, 70,7% (68,0-73,6%). Após ajuste para idade, sexo e cor, a odds ratio para anemia entre H. pylori positivos foi 0,94 (0,70-1,27). Na análise ajustada para sexo, cor, renda familiar, idade e tabagismo, o nível de hemoglobina foi 0,07g/dL menor (-0,24-0,11; p = 0,4) entre H. pylori positivos. Não há associação entre H. pylori e anemia entre adultos usuários de UBS no Sul do Brasil.